Dehalogenative or Deprotonative? The Preparation Pathway to the Organometallic Monomer for Transition‐Metal‐Catalyzed Catalyst‐Transfer‐Type Polymerization of Thiophene Derivatives. Issue 31 (31st March 2020) - Shibuya, Yushin; Mori, Atsunori
Abstract: Due to a wide range of applications in electronic materials, polythiophenes attract considerable attention in organic and polymer syntheses as well as in materials science. For the purpose of developing the practical synthetic protocol, this review focuses on the deprotonative pathway in the preparation of thiophene organometallic monomer, which was shown to be effective employing 2‐halo‐3‐substituted thiophene as a monomer precursor. The thus metallated thiophene monomer was shown to undergo polymerization by nickel(II) complex catalysis, with which highly regioregular head‐to‐tail (HT)‐type polythiophenes were obtained with controlled molecular weight and molecular weight distribution. Several polythiophene derivatives with modified thiophene‐ring and side‐chain structures were shown to be designed in order to achieve the designed functionality as materials. Abstract : Polythiophene synthesis employing cross‐coupling polymerization catalyzed by transition‐metal complexes is reviewed. Generation of organometallic species is available in a dehalogenative or deprotonative manner with a mono‐ or dihalogenated thiophene derivative, among which the deprotonative protocol shows superior atom efficiency in the polymerization.